2014
DOI: 10.1007/s00125-014-3201-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with brain natriuretic peptide prevents the development of cardiac dysfunction in obese diabetic db/db mice

Abstract: Our results indicate that chronic BNP treatment at low dose improves the metabolic profile and prevents the development of myocardial dysfunction in db/db mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 36 publications
9
50
0
1
Order By: Relevance
“…In keeping with this hypothesis, cardiac mRNA expression of both ANP and BNP is reduced in obese Zucker fatty rats and db/db mice (50,55). Data in humans are limited; however, a study in subjects who underwent cardiac catheterization has shown that cardiac BNP release is inversely and independently related to BMI (56).…”
Section: Nps and Obesity Diabetes And Diabetes Complications Obesitymentioning
confidence: 65%
See 3 more Smart Citations
“…In keeping with this hypothesis, cardiac mRNA expression of both ANP and BNP is reduced in obese Zucker fatty rats and db/db mice (50,55). Data in humans are limited; however, a study in subjects who underwent cardiac catheterization has shown that cardiac BNP release is inversely and independently related to BMI (56).…”
Section: Nps and Obesity Diabetes And Diabetes Complications Obesitymentioning
confidence: 65%
“…Indeed, in obese and insulin-resistant subjects, reduced ANP and BNP levels and upregulation of the clearance NPR-C in the adipose tissue may hamper the ability of the local NP system to enhance lipolysis and energy expenditure (5). In keeping with this hypothesis, targeted deletion of the NPR-C gene in rodents results in a lean phenotype, transgenic BNP mice fed with a high-fat diet are protected from obesity and insulin resistance, and chronic BNP infusion improves the metabolic profile of db/db mice, including a reduction in fat content (32,40,50).…”
Section: Nps and Obesity Diabetes And Diabetes Complications Obesitymentioning
confidence: 74%
See 2 more Smart Citations
“…This was associated with increased muscle mitochondrial biogenesis and fat oxidation through upregulation of PPAR‐γ coactivator PGC‐1α and PPAR‐δ. Furthermore, chronic BNP treatment at low dose reduced plasma glucose levels, improved metabolic profile, and prevented development of myocardial dysfunction in obese diabetic mice 100. When BNP levels were determined from HF patients, obese patients indeed had reduced BNP plasma levels, although no difference in severity of HF or proinflammatory cytokine levels were detected 101…”
Section: Natriuretic Peptides In the Regulation Of Energy Metabolismmentioning
confidence: 98%